Novel approaches and strategies for biologics, vaccines, and cancer therapies - Salnikova, Maya; Singh, Manmohan (Elsevier, 2015)
Provides readers with a unique perspective on the successes and challenges that shape the development of novel biologics, vaccines and cancer therapies. This book thoroughly describes advances in the understanding of disease targets and the approaches t